2017
DOI: 10.1002/chir.22784
|View full text |Cite
|
Sign up to set email alerts
|

Hemin and bile pigments are the secondary structure regulators of intrinsically disordered antimicrobial peptides

Abstract: The interaction of protoporphyrin compounds of human origin with the major bee venom component melittin (26 a.a., Z +6) and its hybrid derivative (CM15, 15 a.a., Z +6) were studied by a combination of various spectroscopic methods. Throughout a two-state, concentration-dependent process, hemin and its metabolites (biliverdin, bilirubin, bilirubin ditaurate) increase the parallel β-sheet content of the natively unfolded melittin, suggesting the oligomerization of the peptide chains. In contrast, α-helix promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
4
19
0
Order By: Relevance
“…Our results comparing several lipids above have demonstrated that LPA exerts specific interaction with the investigated peptides, which does not depend merely on its physicochemical properties, as structurally related lysophospholipids have not induced significant structural changes as LPA. Note, that similar selectivity was observed recently in our group when exploring interactions of disordered cationic AMP sequences with small anionic organic molecules, and endogenous bile pigments of hemin and its metabolites 47 , 48 . These studies represent several groups of compounds with similar molecular setup, nevertheless, in all groups we found both compounds which induced drastic conformational changes on AMPs and compounds showing nearly no interaction with the investigated peptides.…”
Section: Resultssupporting
confidence: 84%
“…Our results comparing several lipids above have demonstrated that LPA exerts specific interaction with the investigated peptides, which does not depend merely on its physicochemical properties, as structurally related lysophospholipids have not induced significant structural changes as LPA. Note, that similar selectivity was observed recently in our group when exploring interactions of disordered cationic AMP sequences with small anionic organic molecules, and endogenous bile pigments of hemin and its metabolites 47 , 48 . These studies represent several groups of compounds with similar molecular setup, nevertheless, in all groups we found both compounds which induced drastic conformational changes on AMPs and compounds showing nearly no interaction with the investigated peptides.…”
Section: Resultssupporting
confidence: 84%
“…As it has been shown in our previous reports, the secondary structure of cationic AMPs can deeply be altered by various small molecules [14,15]. Some anionic pharmaceutical agents as well as endogenous metabolites (hemin, bile pigments) were able to induce disorder-to-helix transitions of the bee venom component melittin and its semisynthetic derivative.…”
Section: Introductionmentioning
confidence: 63%
“…According to our previous data [48][49][50], small-molecule-binding-induced disorder-to-helix transitions of cationic AMPs are associated with characteristic CD spectral alterations: In the very first phase of the titration with the folding inducer, the negative CD band of the peptide below 210 nm loses intensity, and its λ min is shifted to longer wavelengths. Similar changes were reported for TFE titration of intrinsically disordered peptides [51] and protein regions [52,53].…”
Section: Circular Dichroism Spectroscopic Evaluation Of the Secondarymentioning
confidence: 91%